Type I fimbriae subunit fimA enhances Escherichia coli biofilm formation but affects L-threonine carbon distribution - Liu, Qingguo; Zhu, Jiaqing; Liu, Na; Sun, Wenjun; Yu, Bin; Niu, Huanqing; Liu, Dong; Ouyang, Pingkai; Ying, Hanjie; Chen, Yong; Zhao, Gulin; Chen, Tianpeng (Frontiers in Bioengineering and Biotechnology, 2022)
Biofilm (BF) provides favourable growth conditions to cells, which has been exploited in the field of industrial biotechnology. Based on our previous research works on type I fimbriae for the biosynthesis of L-threonine (LT) in Escherichia coli, here, a fimA-overexpressing strain was engineered, which improved BF formation under the industrial fermentation conditions. The morphological observation and characterization of BF formation were conducted to verify the function of subunit FimA. However, it was not suitable for repeated-batch immobilized fermentation, as LT titre was not elevated significantly. The underlying molecular mechanisms of BF formation and LT carbon flux were explored by transcriptomic analysis. The results showed that fimA regulated E. coli BF formation but affected LT carbon distribution. This study will stimulate thoughts about how fimbriae gene regulated biofilms and amino acids excretion and bring some consideration and provide a reference for the development of BF-based biomanufacturing processes in E. coli.